Rattus xanthurus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus xanthurus (Gray, 1867). Proc. Zool. Soc. Lond., 1867:598. TYPE LOCALITY: Indonesia, N. Sulawesi, Tondano, 1100 m. DISTRIBUTION: Sulawesi. COMMENT: Includes paraxanthus and faberi; see Musser, 1973, Am. Mus. Novit., 2511:24. Sody, 1941, Treubia, 18(2):260, included xanthurus in Taeromys; but see comment under Taeromys. ISIS NUMBER: 5301410011058115001 as Taeromys xanthurus. 5301410011058088001 as R. paraxanthurus (sic). Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 554, DOI: 10.5281/zenodo.7353037